Bone Marrow Soluble Immunological Mediators as Clinical Prognosis Biomarkers in B-Cell Acute Lymphoblastic Leukemia Patients Undergoing Induction Therapy - Kerr, Marlon Wendell Athaydes; Magalhães-Gama, Fábio; Ibiapina, Hiochelson Najibe Santos; Hanna, Fabíola Silva Alves; Xabregas, Lilyane Amorim; Alves, Eliana Brasil; Pimentel, João Paulo Diniz; Carvalho, Maria Perpétuo Socorro Sampaio; Tarragô, Andréa Monteiro; Teixeira-Carvalho, Andréa; Martins-Filho, Olindo Assis; da Costa, Allyson Guimarães; et al. (Frontiers in Oncology, 2021)
Different factors are used as predictors of unfavorable clinical outcomes in B-Cell Acute Lymphoblastic Leukemia (B-ALL) patients. However, new prognostic markers are needed in order to allow treatment to be more accurate, providing better results and an improved quality of life. In the present study, we have characterized the profile of bone marrow soluble mediators as possible biomarkers for risk group stratification and minimal residual disease (MRD) detection during induction therapy. The study featured 47 newly-diagnosed B-cell acute lymphoblastic leukemia (B-ALL) patients that were categorized into subgroups during induction therapy according to risk stratification at day 15 [Low Risk (LR), Low Risk increasing to High Risk (LR→HR) and High Risk (HR)] and the MRD detection on day 35 (MRD(-) and MRD(+)). Soluble immunological mediators (CXCL8, CCL2, CXCL9, CCL5, CXCL10, IL-1β, IL-6, TNF, IFN-γ, IL-17A, IL-4, IL-5, IL-10 and IL-2) were quantified by cytometric bead array and ELISA. Our findings demonstrated that increased levels of CCL5, IFN-γ and IL-2 at baseline appeared as putative candidates of good prognosis in LR and MRD(-) subgroups, while CCL2 was identified as a consistent late biomarker associated with poor prognosis, which was observed on D35 in HR and MRD(+) subgroups. Furthermore, apparently controversial data regarding IL-17A and TNF did not allow the definition of these molecules as either positive or negative biomarkers. These results contribute to the search for novel prognostic indicators, and indicate the potential of bone marrow soluble mediators in prognosis and follow-up of B-ALL patients during induction therapy.